Updated Framework on The Dissemination of Capacity Development Information. (Policy Papers; Policy Paper ;, 2022)
The IMF's capacity development (CD) information dissemination policy needs to adapt to a new landscape. The Fund is providing more CD and producing greater and more diverse types of CD-related information. Meanwhile, the external landscape has also evolved, as members, partners, and other CD providers increasingly expect greater transparency and access to information. This paper sets out envisaged reforms to further widen the dissemination and publication of CD information.